An Arthrobacter citreus strain suitable for degrading ε-caprolactam in polyamide waste and accumulation of glutamic acid - Baxi, Nandita N. (AMB Express, 2019)
ε-Caprolactam-a toxic xenobiotic compound present in industrial polyamide waste was found to be degraded by caprolactam-degrading bacteria. Arthrobacter citreus was able to utilize up to 20 g ε-caprolactam/l as the sole source of carbon more efficiently as compared to the other Gram positive caprolactam-degrading bacteria Rhodococcus rhodochrous and Bacillus sphaericus. The cells of A. citreus remained viable in medium up to 40 g caprolactam/l. The degradation of 10 g caprolactam/l by A. citreus, when supplied as the sole source of carbon and nitrogen lead to the formation of 6-aminocaproic acid which was detected in broth and there was also an increase in the ammonium content. One of the other metabolites found to consistently accumulate in extracellular medium during the utilization of caprolactam by A. citreus was glutamic acid, though not reported in case of other caprolactam-degrading bacteria. A. citreus could metabolise caprolactam to form non toxic products such as 6-aminocaproic acid and glutamic acid which are amino acids of physiological and commercial importance. In the presence of 6-aminocaproic acid, the rate of caprolactam utilization by A. citreus was decreased but not inhibited and the viable count of cells was found to increase using both the substrates simultaneously. A. citreus was also suitable for degradation of caprolactam in presence of low phosphate as prevalent in soil, and in sterile soil without the supplementation of any other carbon or nitrogen, as well as in native non sterile soil where other microorganisms are present.